2008
DOI: 10.1159/000148221
|View full text |Cite
|
Sign up to set email alerts
|

Role of Physical Chemical Properties in Drug Relay into Skin Compartments

Abstract: The ability of a drug to reach the interstitial fluid is an important aspect of drug efficacy – as a possible indicator of skin and cell compartment concentration. This overview addresses the relationship of the physical properties of several antibiotics to their ability to enter the interstitial fluid utilizing a cantharidin blister model. By collecting pharmacokinetic data for 12 antibiotics administered orally and 11 intravenously, we compared the fraction of drug that reaches the interstitial fluid (AUC Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…We suspect that much remains to be learned regarding other barriers and mechanisms. The ion data, here, alongside work by Fortenbach et al., 21 Cunico et al., 23 and Wilson et al., 24 provide impetus to enlarge our barrier understandings. We suspect that the situation of skin barriers may resemble that of our knowledge of transporters; the first transporter superfamily, the ATP‐binding cassette transporters, was recognized 24 years ago, 25 and today over 400 transporters have been discovered.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…We suspect that much remains to be learned regarding other barriers and mechanisms. The ion data, here, alongside work by Fortenbach et al., 21 Cunico et al., 23 and Wilson et al., 24 provide impetus to enlarge our barrier understandings. We suspect that the situation of skin barriers may resemble that of our knowledge of transporters; the first transporter superfamily, the ATP‐binding cassette transporters, was recognized 24 years ago, 25 and today over 400 transporters have been discovered.…”
Section: Discussionsupporting
confidence: 56%
“…Beyond the percutaneous egression of ions, Fortenbach 21 examined a drug's physicochemical properties in relation to its delivery to the skin using cantharidin blister fluid. There was no statistically significant correlation between a drug's partition coefficient and the fraction penetrating into the epidermal interstitial fluid, which was calculated by dividing AUC blister by AUC serum .…”
Section: Discussionmentioning
confidence: 99%
“…Author Property/chemical Summary Fortenbach et al (2008) Hydrophobicity, serum concentration Hydrophobic nature of drug had no eff ect on its ability to reach interstitial fl uid; serum concentration displayed a strong linear correlation to a drug's interstitial fl uid concentration Maibach and Feldmann (1969) Hydrocortisone, testosterone, and benzoic acid Increased concentrations of a topically applied drug always resulted in larger amounts of absorption Wester and Maibach (1976) Hydrocortisone, testosterone, and benzoic acid Increased concentrations of drug decreased the effi ciency of percutaneous absorption Bronaugh and Maibach (2002) Hydrocortisone Triple daily dosage produced greater hydrocortisone absorption compared with a single dose and a single large dose Bronaugh and Maibach (2002) Hydrocortisone There was a highly signifi cant linear correlation between total amount of chemical penetration within 4 days and the amount present in the SC at the end of the 30 min application time Feldmann and Maibach (1967); Maibach et al (1971) Hydrocortisone, malathion, parathion Showed penetration in decreasing order of genitals, head, trunk, arms and lastly legs Rinn et al (2006) Fibroblasts Clustering was shown to exist based on anterior-posterior positioning relative to the body axis; proximal-distal spacing along individual limbs; and dermal-nondermal, comparing limbs to organs Yosipovitch et al (2000) Variations in neonates Compared with adults, the neonates had lower TEWL values in all areas except the forearm; for SC hydration, neonates had signifi cantly lower values in the forehead, back and abdomen, and higher values in the forearms and palms after day 1 compared with adults; skin surface pH was signifi cantly higher in neonates than adults in all body sites Anatomic and characteristic variations in dermal and chemical properties Dermatotoxicologic science will signifi cantly mature when we have the opportunity to extend our knowledge of skin barriers -from that of water loss (TEWL) to the numerous other barriers, some of which are summarized here.…”
Section: Resultsmentioning
confidence: 99%
“…A careful examination of the barrier's chemical properties as related to the efficacy of drug delivery could provide insight into improving current dermatologic therapy. Fortenbach et al (2008) examined the ability of orally and intravenously administered drugs to reach the skin's interstitial fl uid. The eff ects of hydrophobicity and serum concentration were explored using a cantharidin blister model to emulate interstitial fl uid.…”
Section: Percutaneous Movement (Penetration and Egression)mentioning
confidence: 99%
“…The maximum detection depth is 250 µm. The focus position is manually adjustable on the handpiece [23][24][25]. This permits various dermal layers to be analyzed and the data acquired also in the dimension of depth.…”
Section: In Vivo Laser Scanning Microscopymentioning
confidence: 99%